Maize productivity (Diamantes 8843) under different planting densities and nitrogen doses - Lázaro-Rojas, Wendy (2022)
Introduction. In Costa Rica, maize (Zea mays) is an important component of the population’s diet. However, the planting area has been reduced due to marketing policies and reduced knowledge of agronomic management of the crop. Objective. To analyze the effect of N doses and planting densities on the productivity of maize variety Los Diamantes 8843 in Santa Cruz, Guanacaste, Costa Rica. Materials and methods. The study was carried out between August and December 2018 at the Santa Cruz Experimental Farm, Universidad de Costa Rica. In a randomized complete block design, three planting densities: 50,000, 57,143, and 66,666 plants/ha and four increasing doses of N: 0, 100, 200, and 300 kg ha-1 were evaluated. Plant height, plant fresh weight, stem thickness, cob quality, nutrient uptake and yield were quantified. An analysis of variance was adjusted for each variable. Results. There was a significant effect of N dose over the variables height, dry weight, number of grains per row, number of ears per useful plot, and nutrient uptake. In general, these variables were higher at high N doses. There was significant effect of planting density on height, number of ears, and nutrient uptake, these variables reached higher values at high densities. Higher efficiency rates were achieved at 100 kg ha-1 and at a density of 50,000 plants/ha. The yield was lower in any of the evaluated densities, when N was not applied. The doses of 100 and 200 kg ha-1 showed the highest yields, regardless of planting density. Conclusion. The dose of 100 kg ha-1 of N and the density of 57 143 plants/ha showed the highest values for the efficiency indices and the highest yield.